مستوى مهارات التفكير الناقد لدى تلامذة الصف الرابع الأساسي في مادة الرياضيات وعلاقته بمتغيري الجنس والبيئة "دراسة ميدانية في مدارس التعليم الأساسي بمحافظة اللاذقية" (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت الدراسة إلى تعرف مستوى مهارات التفكير الناقد(تعرف الافتراضات، والتفسير، والاستنتاج، والاستنباط، وتقويم الحجج) لدى تلامذة الصف الرابع الأساسي، وأثر الجنس والبيئة على هذا المستوى. ولتحقيق ذلك، تم استخدام المنهج الوصفي التحليلي، وتم اعداد  مقياس لمهارات التفكير الناقد، حيث تم التأكد من صدقه وثباته، ووزع على عينة قوامها (127)  تلميذاً وتلميذة من تلامذة الصف الرابع الأساسي في محافظة اللاذقية. وأظهرت النتائج أن عينة البحث تمتلك مهارات التفكير الناقد المدروسة بمستوى ضعيف، وتبين عدم وجود أي فرق ذي دلالة إحصائية عند مستوى دلالة (P=0.05) بين متوسطي درجات الذكور والإناث، كما توصلت هذه الدراسة إلى أن تلامذة الريف يمتلكون مهارات التفكير الناقد بدرجة أكبر مما يمتلكها تلامذة المدينة، أوصى القيام بتدريس مهارات التفكير الناقد . The purpose of this study is to examine the level of critical thinking skills (recognition of assumptions, interpretation, deduction, inference, evaluation of argument), by fourth graders in mathematics, and investigate the effect of gender and living environment( country side, city). To that end, the researchers use the analytical descriptive method, preparing reliable, valid scales to measure critical thinking skills, the sample used consists of (127) students' in Lattakia. The results show that students poorly perform critical thinking skills (recognition of assumptions, interpretation, deduction, inference, evaluation of argument). Also, this study shows no significant difference(p=0.05) between male and female students' average scores, Rural students on the scale of critical thinking skills are better than city students, The researchers suggest  teaching critical thinking skills.